Bimatrix game model for the selection of investment portfolio - Vakarinienė, Sigutė; Misevičius, Gintautas (Lietuvos matematikos rinkinys, 2009)
This research suggests a Nash equilibria model for the selection of investment portfolios. The components of portfolio are found by solving linear programming task with binary variables. In the experimental part of the research ineffective portfolios exerted from this model are tested referring to the statistical data of the stock market indexes of several countries. Realizations of the suggested portfolios are compared to realizations of effective portfolios.